The Relationship between Humans and Animals in the Aboriginal Mythology through the Prism of Animal Studies - Siewierski, Radosław (Journal of Education Culture and Society, 2022)
Aim. The aim of this article is to analyse Aboriginal myths and discover the relationship between animals and humans in the beliefs of the indigenous Australians. The article attempts to explain how animals are described when compared to people and vice. Furthermore, the author endeavours to establish what the relationship looks like and how it is presented.  Methods. As Aboriginal myths and mythologies have been evolving for hundreds and thousands of years, it is not possible to analyse every single myth. Hence, in order to narrow them down, only the myths presented by Alexander Wyclif Reed will be analysed. The analysis will be conducted from the perspective of Animals Studies, with a particular focus on the contemporary ecological views presented by a contemporary representative of an ecological turn and animal rights scholar, Peter Wohlleben. The analysis will focus on three main aspects: parenting/motherly love, instincts, feelings and emotions.  Results. The analysis shows that animals were of the utmost importance in the Aboriginal everyday life and most of the time were treated on a par with humans. Just like the Aboriginal point of view, contemporary attitude to Animal Studies attempts to alter the view according to which animals are devoid of feelings and intelligence.  Conclusions. Animals seem to have a crucial role in every aspect of Aboriginal everyday life, including religious and social. They were not perceived as lesser or worse; conversely, Aboriginals considered them to be as intelligent and significant as the Aboriginal people themselves.